Aplicação de técnicas de Data Mining para auxiliar no processo de fiscalização no âmbito do Tribunal de Contas do Estado da Paraíba - Grilo Júnior, Tarcísio Ferreira (2010)
This search has as goal to validate the hypothesis of the applicability of data mining techniques in Bidding and Contracts database managed by the Account Court of Paraiba State, enabling the generation of rules and discovery of hidden knowledge or implicit, contributing to the process of decision making, supervision and celerity in this Court of Auditors. To the best comprehension of this work, It was made a literature revision bringing at first place a historic vision about the decision process, as well as this theme evolution studies and the relation between the tender processes sent to Account Court of Paraiba State and the fraud indication discovery process and irregularities through the data mining process using. We will bring to light the concept of Business Intelligence (BI) and for it`s main components, as well as the concepts of knowledge discovery in database, and a comparing between the using of the instruments of data mining. We expect from this implant of the data mining an increase in the productivity and also an increase in speed of lawsuit process from the public accounts analysis and public money fiscal control.